2021
DOI: 10.1123/japa.2020-0177
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Physical Activity Among Older Adults in the European Union

Abstract: The study aimed to ascertain the levels of older European people’s physical activity according to sociodemographic variables. The sample size was 7,893 citizens aged 65 and over from the European Union. The participants were classified as physically inactive, adequately active, or highly active, according to the World Health Organization. The total metabolic equivalents of task minutes per week were also calculated. In the results, 55.5% of older people were adequately active, and 43.8% were highly active, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Similar categorization has been followed by other European studies (i.e. Clemente Remón et al , 2020 ). Finally, the individual classification has been regionalized, estimating for each region the percentage of non-active individuals as well as individuals with below-healthy, healthy and extra-healthy levels of PA. Table 1 shows an overview of the four PA regional indicators.…”
Section: Methodssupporting
confidence: 52%
See 1 more Smart Citation
“…Similar categorization has been followed by other European studies (i.e. Clemente Remón et al , 2020 ). Finally, the individual classification has been regionalized, estimating for each region the percentage of non-active individuals as well as individuals with below-healthy, healthy and extra-healthy levels of PA. Table 1 shows an overview of the four PA regional indicators.…”
Section: Methodssupporting
confidence: 52%
“…Only few papers have developed a regional approach in Europe (i.e. Lera-López and Marco, 2018 ; Clemente Remón et al , 2020 ) despite regional differences and the role played by regional characteristics in explaining PA ( Kokolakakis et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, a decline in physical fitness above the norm, usually occurring in inactive people, can lead to the elderly experiencing great difficulties in coping with utilitarian domestic and self-care activities; this can hamper their own ability to meet their needs and incur greater state expenditure on medical care and social assistance. For seniors, maintaining an appropriate level of physical fitness allows them to retain their independence and the possibility of self-fulfillment [1,17].…”
Section: Of 12mentioning
confidence: 99%
“…In Poland, as in other countries with varied societies and economies, both in Europe and beyond, physical activity (PA) remains at an unsatisfactory level among seniors [1].…”
Section: Introductionmentioning
confidence: 99%
“…This is because increased age involves declining PA and increased chronic disease risk ( 9 ). A study of older European people's PA showed that nearly half of the elderly population was not adequately active ( 10 ). Another study that examined the PA levels of adults over 50 in 6 low- and middle-income countries reported that of the 34,129 respondents, only 23.5% met the recommended PA level ( 11 ).…”
Section: Introductionmentioning
confidence: 99%